Das grüne Paradoxon: Warum man das Angebot bei der Klimapolitik nicht vergessen darf - Hans-Werner Sinn (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2008)
– Despite its efforts and obligations under the Kyoto Protocol, the EU has not succeeded in even making a dent in the rapidly rising trend of worldwide carbon dioxide emissions. If anything, the trend has accelerated in recent years. In his Thünen Lecture given to the German Economic Association in October 2007, the author criticizes the attempt to slow down global warming by means of unilaterally curtailing the demand for fossil fuels and develops an intertemporal supply side approach to the economics of global warming. He advances the hypothesis that the ineffectiveness of demand policies results from anticipation effects on the part of the owners of fossil fuel resources. In addition to the threat of potential ousting by domestic rivals, the threat of falling energy prices (against a modified Hotelling trend) due to greening public policies and increasing participation in world wide emissions trading systems gives resource ownersthe incentive to speedup extraction. Feasible policy measures that do not encounter such problematic anticipation effects include the rapid creation of a complete worldwide monopsony for fossil fuels that can dictate quantities rather than having to rely on price signals. Moreover, source taxes on the financial returns of resource owners will provideadditional conservation motives; technical measures including afforestation andsequestration may also be a way to reduce the speed of global warming.
Keywords: H23; O13; Q32; Q54; 330